2007
DOI: 10.1002/jae.960
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐nonparametric competing risks analysis of recidivism

Abstract: SUMMARYIn this paper we specify a semi-nonparametric competing risks (SNP-CR) model of recidivism, for misdemeanors and felonies. The model is a bivariate mixed proportional hazard model with Weibull baseline hazards and common unobserved heterogeneity. The distribution of the latter is modeled seminonparametrically, using orthonormal Legendre polynomials on the unit interval, and integrated out to make the two durations dependent, conditional on the covariates. The SNP-CR model involved corresponds to a Logit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…See Newey (1990) for a general review of efficiency bounds, and Hahn (1994) and Ridder and Woutersen (2003) for the efficiency bound of the MPH model. On the other hand, Hahn (1994) has also shown that, in general, the multiple spell MPH model does not suffer from this problem, which is confirmed by the estimation results in Bierens and Carvalho (2007). Thus, Assumptions 6.7 and/or 6.8 may not hold for the single spell MPH model, and the same applies to Assumption 3(a) in Chen et al (2006) (cf.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…See Newey (1990) for a general review of efficiency bounds, and Hahn (1994) and Ridder and Woutersen (2003) for the efficiency bound of the MPH model. On the other hand, Hahn (1994) has also shown that, in general, the multiple spell MPH model does not suffer from this problem, which is confirmed by the estimation results in Bierens and Carvalho (2007). Thus, Assumptions 6.7 and/or 6.8 may not hold for the single spell MPH model, and the same applies to Assumption 3(a) in Chen et al (2006) (cf.…”
Section: Discussionsupporting
confidence: 58%
“…The model then becomes fully parametric, and, therefore, asymptotic normality can be derived in a standard way, provided that the SNP parameters involved are unique. This is the approach followed by Bierens and Carvalho (2007).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the recidivism literature, failure is often defined as reentry to the criminal justice system, whereas recidivism time is often measured examining the time between release from prison and the first rearrest (Bierens & Carvalho, 2007). In studying recidivism with survival analysis, an assessment of the hazard function of recidivism is needed as well (Gruenewald & West, 1989).…”
Section: The Use Of Survival Analysismentioning
confidence: 99%
“…We used that technique in the application for the JAE, and I also managed to squeeze in an ICM test for the correctness of the Weibull baseline hazards. It became a nice paper [19], an empirical application with theoretical innovations as required by the JAE. That is how I got interested in semi-nonparametric econometrics.…”
mentioning
confidence: 99%